2018
DOI: 10.1111/jsap.12939
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short‐term complications between unilateral and single‐session bilateral surgery for medial patellar luxation in small/medium breed dogs

Abstract: Objectives To compare the short‐term complications of unilateral versus single‐session bilateral medial patellar luxation surgery in small dogs. Materials and Methods The medical records of dogs weighing less than 13∙6 kg that underwent medial patellar luxation surgery were reviewed. Dogs were included in one of two groups based on the type of surgery performed (unilateral or single‐session bilateral). Postoperative patellar luxation grade and complications were compared between the groups. Results Two hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
7
3
Order By: Relevance
“…5,6,[11][12][13][14]23 In these publications, the incidence of major implant-related complications and tibial tuberosity avulsions or fractures were 3 to 17% and 2 to 6%, respectively, whereas implant-related complications or tibial tuberosity avulsions or fractures were not observed in our study. 5,6,[11][12][13][14]23 Sparse data on other TTT fixation methods are available. A craniocaudal screw placed through the tibial tuberosity in addition to Kirschner wires was associated with a higher risk of major complications, although the number of cases was low.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…5,6,[11][12][13][14]23 In these publications, the incidence of major implant-related complications and tibial tuberosity avulsions or fractures were 3 to 17% and 2 to 6%, respectively, whereas implant-related complications or tibial tuberosity avulsions or fractures were not observed in our study. 5,6,[11][12][13][14]23 Sparse data on other TTT fixation methods are available. A craniocaudal screw placed through the tibial tuberosity in addition to Kirschner wires was associated with a higher risk of major complications, although the number of cases was low.…”
Section: Discussioncontrasting
confidence: 42%
“…Complications were defined as any unfavorable and unplanned event, sign, or disease related to treatment, classified by timeframe as either intraoperative, immediately postoperative (between surgery and discharge), short term (between discharge and 3 months postoperative) or long term (!3 months postoperatively) and graded as minor when resolved spontaneously or with medical treatment only or as major when surgical treatment was indicated. 6,12,13 In cohort A, owners were asked to complete the Liverpool Osteoarthritis in Dogs (LOAD) questionnaire before surgery and at 6 weeks and 3 months after surgery. 20 Outcome was categorized as excellent when function at last follow-up was normal, good when function was near normal with infrequent lameness, acceptable with grade 1 lameness and unacceptable with higher-grade lameness or the need for analgesics.…”
Section: Follow-upmentioning
confidence: 99%
“…9 Bilateral single-stage surgery lowers treatment cost, requiring only a single anaesthetic episode and recovery period. 21 Compared to bilateral staged surgery, there is also the potential to halt disease progression of the contralateral limb during recovery 22 while providing immediate relief to both limbs. At least in small breed dogs, bilateral single-session procedures did not increase hospitalisation periods compared to unilateral procedures.…”
Section: Discussionmentioning
confidence: 99%
“…23,22 Another study 24 calculated an odds ratio of 1.8 for total complications and 1.2 for major complications in cases of concurrent bilateral MPL correction compared to unilateral procedures; however, these odds ratios did not achieve statistical significance and the authors did not conclude that bilateral concurrent correction led to increased complications. Sanders and Bevan 21 argues that bilateral single session MPL repair places excessive implant stress due to increased load from early limb use, predisposing to major complications. Data from that study demonstrated that bilateral single-session MPL had increased minor and major complications rates of 7 and 24%, respec-tively, compared to 5 and 13%, respectively, for unilateral surgery, however these proportions were directly compared without relevant statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation